Bipedal locomotion in zoo apes: Revisiting the hylobatian model for bipedal origins. (14th March 2022) - Rosen, Kyle H.; Jones, Caroline E.; DeSilva, Jeremy M.
Abstract: Abstract: Bipedal locomotion is a hallmark of being human. Yet the body form from which bipedalism evolved remains unclear. Specifically, the positional behaviour (i.e. orthograde vs. pronograde) and the length of the lumbar spine (i.e. long and mobile vs. short and stiff) of the last common ancestor (LCA) of the African great apes and humans require further investigation. While fossil evidence would be the most conclusive, the paucity of hominid fossils from 5–10 million years ago makes this field of research challenging. In their absence, extant primate anatomy and behaviour may offer some insight into the ancestral body form from which bipedalism could most easily evolve. Here, we quantify the frequency of bipedalism in a large sample ( N = 496) of zoo-housed hominoids and cercopithecines. Our results show that while each studied species of ape and monkey can move bipedally, hylobatids are significantly more bipedal and engage in bipedal locomotion more frequently and for greater distances than any other primate sampled. These data support hypotheses of an orthograde, long-backed and arboreal LCA, which is consistent with hominoid fossils from the middle-to-late Miocene. If true, knuckle-walking evolved in parallel in Pan and Gorilla, and the human body form, particularly the long lower back and orthograde posture, is conserved.